Plasticity of root growth and respiratory activity: Root responses to above-ground senescence, fruit removal or partial root pruning in soybean - Fanello, Diego Darío (2020)
This work focuses on the alterations in soybean root growth and activity during whole plant senescence and the contribution of roots to source-sink relations during plant development. The experiments were designed to analyze the activity of roots in relation to: a) whole plant senescence, b) total pod removal and c) root pruning (15, 25 and 50% of DW) during seed growth stages. Roots can grow until an advanced R5 stage and their specific activity decreases along the reproductive development but whole root activity declines from R6. However root respiration is maintained at a basal level until R8. Depodded plants showed a large increase of root dry matter (about 470%) and a large increase of AOX protein. Root pruning treatments showed a proportional increase of specific root respiration in 25 and 50% treatments but no differences of whole root respiration and dry matter partitioning at R7. These results indicate that roots are under the control of the requirements of above ground organs until final stages of seed growth but, after this, roots may survive independently for some time. This suggests that roots do not suffer a senescence-like process as leaves do. Also, plants have a high capacity to buffer changes in root biomass production and specific root activity under pod removal or partial root pruning.